2021
DOI: 10.3390/jcm10153432
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Growth after Direct Pulp Capping with the Different Fractions of Plasma Rich in Growth Factors (PRGF) vs. MTA: Experimental Study in Animal Model

Abstract: Background: This study aimed to evaluate the area of dentin growth in rabbit incisors after pulp capping with plasma rich in growth factors (PRGF) compared with mineral trioxide aggregate (MTA) by fluorescence. Methods: twenty-seven upper and lower incisors of rabbits were divided into 4 groups: poor PRGF (F1) (n = 9 teeth), rich PRGF (F2) (n = 8 teeth), ProRoot MTA (positive control, n = 5 teeth), and untreated (NC) (negative control, n = 5). Fluorochrome markers were injected 24 h before surgery and the day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…1 Post-injury pulp repair requires multiple growth factors, including BMP-2, BMP-4, BMP-7/OP-1, FGF-2, IGF-1, and -2, and TGF-b1, to induce the formation of tertiary dentinogenesis. 19 Direct pulp-capping is a treatment procedure to maintain pulp vitality and form reparative dentin after exposure, either traumatically or mechanically, without inducing inflammation using biomaterials. [3][4][5] The objective of direct pulp-capping treatment is to produce regeneration at the injured area of dental pulp by creating dentinal bridges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Post-injury pulp repair requires multiple growth factors, including BMP-2, BMP-4, BMP-7/OP-1, FGF-2, IGF-1, and -2, and TGF-b1, to induce the formation of tertiary dentinogenesis. 19 Direct pulp-capping is a treatment procedure to maintain pulp vitality and form reparative dentin after exposure, either traumatically or mechanically, without inducing inflammation using biomaterials. [3][4][5] The objective of direct pulp-capping treatment is to produce regeneration at the injured area of dental pulp by creating dentinal bridges.…”
Section: Discussionmentioning
confidence: 99%
“…3 The application of permanent restoration directly after pulp-capping treatment can be a determining factor in successful treatment. 19…”
Section: Discussionmentioning
confidence: 99%
“…the dose of general anesthesia calculated according to each animal weight, using of Intra muscular injection of xylazine HCl 2% (5 mg/kg), followed by another of Ketamine HCL( 35 mg/kg) to induce general anesthesia, after achieving good sedation, Class V cavities were prepared in the cervical buccal surface 1 mm incisal to the marginal gingiva by using of a high-speed round diamond 0.8 mm carbide tungsten bur (Komet Dental, Lemgo, Germany) with intermittent drilling under irrigation with sterile normal saline, drilling done at a 45 degrees inclination apically and extended for the pulp chamber, the pulp exposure done by using small spoon excavator, removing part of pulp tissue , the cavity formed is approximately of 2 mm depth necessary to apply capping material with final restoration, 30 the bleeding at the exposure site was controlled by irrigation with 5.25% concentration of NaOCl for 30 Sc then the cavity washed with distilled water and dry by brief air blot, the cavity of Group I left empty and just covered with resin modified glass ionomere cement were cured for 30 Second and the cavity of Group II filled with paste-like mixture of the novel cement then covered with resin modified glass ionomere cement were cured for 30 Second. 30,31 Histologic Assessment: Six rabbits were euthanized per interval by intravenous injection with anaesthetic overdose. Jaws were fixed in 10% neutral buffered formalin, decalcified in 10% nitric acid for 3 days, dehydrated sequentially in graded alcohols, 70%, 80%, 90%, and 100%, then immersed in xylene, and finally embedded in paraffin blocks.…”
Section: Methodsmentioning
confidence: 99%
“…MTA-based products show discrete antimicrobial activity compared to calcium hydroxide-based materials, which show higher antimicrobial activity [27] . One study showed that the application of PRGF-rich and PRGF-poor fraction as pulp capping material, stimulated dentin formation more strongly than MTA and untreated negative control [28] . A study compared MTA and HA / β-TCP / C local action, being similar to that of MTA, when used as a vital pulp treatment agent in terms of absence of inflammation and maintenance of pulp vitality, although there are significant differences between the two materials in terms of dentin bridging [29] .…”
Section: Mtamentioning
confidence: 99%